2014
DOI: 10.1021/jm401802f
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Evaluation of 5HT2C Agonists, [11C]WAY-163909 and [11C]Vabicaserin, Formed by Pictet–Spengler Cyclization

Abstract: The serotonin subtype 2C (5HT2C) receptor is an emerging and promising drug target to treat several disorders of the human central nervous system. In this current report, two potent and selective 5HT2C full agonists, WAY-163909 (2) and vabicaserin (3), were radiolabeled with carbon-11 via Pictet–Spengler cyclization with [11C]formaldehyde and used in positron emission tomography (PET) imaging. Reaction conditions were optimized to exclude the major source of isotope dilution caused by the previously unknown br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 31 publications
0
30
0
1
Order By: Relevance
“…The aim of the present study, therefore, was to evaluate the effects of the highly selective serotonin 5-HT 2C receptor agonist WAY163909 (Dunlop et al 2005; Neelamegam et al 2014) on the behavioral neuropharmacology of cocaine and methamphetamine in rhesus monkeys. Studies have shown that WAY163909 exhibits excellent binding affinity ( K i of ∼10 nM) and functional selectivity for the human 5-HT 2C receptor (Dunlop et al 2005), being one of the most selective agents identified to date compared with other compounds reported in the literature, including Ro 60-0175 (Martin et al, 1998) and novel compounds such as lorcaserin (Thomsen et al, 2008) and vabicaserin (SCA-136) (Dunlop et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study, therefore, was to evaluate the effects of the highly selective serotonin 5-HT 2C receptor agonist WAY163909 (Dunlop et al 2005; Neelamegam et al 2014) on the behavioral neuropharmacology of cocaine and methamphetamine in rhesus monkeys. Studies have shown that WAY163909 exhibits excellent binding affinity ( K i of ∼10 nM) and functional selectivity for the human 5-HT 2C receptor (Dunlop et al 2005), being one of the most selective agents identified to date compared with other compounds reported in the literature, including Ro 60-0175 (Martin et al, 1998) and novel compounds such as lorcaserin (Thomsen et al, 2008) and vabicaserin (SCA-136) (Dunlop et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Polyheterocyclic scaffold synthesis has attracted ongoing interest due to its application in drug discovery and material sciences . For example, Herbertenolide possesses anti‐tumor activity in vivo against KREBS II ascetic tumor and cytotoxicity in vitro against HTC hepatoma cells (Figure ) . As a result, much effort has been devoted towards constructing polyheterocyclic skeletons .…”
Section: Introductionmentioning
confidence: 99%
“…There are several attempts recently made for the development of 5-HT 2C R PET tracers with limited success. These include a low affinity azetidine analogue of pyrimidoazepine, a 5-HT 2C agonist (K i = 75 nM) and antagonists WAY-163909 (K i = 10 nM) and vabicaserin (K i = 3 nM) [124, 125]. The radiosynthesis of [ 11 C]pyrimidoazepine has been achieved via [ 11 C]methylation using [ 11 C]CH 3 I, whereas the antagonist ligands were synthesized via a novel C-11 Pictet-Spengler cyclization with [ 11 C]CH 2 O ([124, 125].…”
Section: Introductionmentioning
confidence: 99%